Prospects on Repurposing a Live Attenuated Vaccine for the Control of Unrelated Infections - Seo, Sang-Uk; Seong, Baik-Lin (Frontiers in Immunology, 2022)
Live vaccines use attenuated microbes to acquire immunity against pathogens in a safe way. As live attenuated vaccines (LAVs) still maintain infectivity, the vaccination stimulates diverse immune responses by mimicking natural infection. Induction of pathogen-specific antibodies or cell-mediated cytotoxicity provides means of specific protection, but LAV can also elicit unintended off-target effects, termed non-specific effects. Such mechanisms as short-lived genetic interference and non-specific innate immune response or long-lasting trained immunity and heterologous immunity allow LAVs to develop resistance to subsequent microbial infections. Based on their safety and potential for interference, LAVs may be considered as an alternative for immediate mitigation and control of unexpected pandemic outbreaks before pathogen-specific therapeutic and prophylactic measures are deployed.